PENGARUH REBUSAN DAUN SIRIH TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI DI DESA PASURUHAN KECAMATAN MERTOYUDAN KABUPATEN MAGELANG - Sigit Priyanto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Elderly (elderly) is a group of people who experience a process of gradual change over a period of time and are at risk of experiencing various health problems. Problems that are often experienced by elderly people are malnutrition, balance disorders, and the cardiovascular system, namely hypertension. Objective: To determine the effect of betel leaf decoction on blood pressure reduction in elderly hypertension in Pasuruhan village, Mertoyudan district, Magelang regency. Method: The research design used in this study was a quasi experiment using two groups pre post test with control group design. The number of samples was 36 for the intervention group and 36 for the control group. Hypothesis test analysis using Wilcoxon test analysis. Results: The results of statistical tests showed the effect of betel leaf decoction on blood pressure reduction in elderly hypertension in Pasuruhan village, Mertoyudan district, Magelang regency. p-value = 0.000 (<0.05), with a mean pre-test of 167/115 mmHg and post-test was 157/105 mmHg in the intervention group. The average control group of blood pressure before treatment was 169/119 mmHg and after treatment was 162/113 mmHg. Conclusion: There is an effect of betel leaf decoction on decreasing blood pressure in elderly hypertension in Pasuruhan village, Mertoyudan district, Magelang regency. Suggestion: Decoction of betel leaf can be given as a support therapy for hypertensive patients.